(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to evaluate the perceived effectiveness of an AI HR helpdesk among teaching and non-teaching employees at Bestlink College of the Philippines. The study employed a quantitative research design, with a survey questionnaire as the primary data- gathering tool. The questionnaire assessed the participants’ perception of the AI HR helpdesk’s effectiveness in addressing their HR concerns, as well as their satisfaction with the overall function. The results of the study suggest that both teaching and non-teaching employees perceive the AI HR helpdesk as an effective means of addressing their HR concerns. The participants reported high levels of effectiveness with the AI HR helpdesk’s HR support, Easy access information, Data Privacy, Ticketing System, Availability, and automated repetitive tasks in providing HR-related information and assistance. However, the study also identifies some areas for improvement, such as the need for more human-like interactions with the AI HR helpdesk. The study’s findings provide valuable insights for organizations that are considering implementing AI HR helpdesk systems. The study’s results can guide organizations in developing and implementing effective AI HR helpdesk systems that meet their employees’ needs and preferences. Based on the overall findings, most of the 190 respondents agree to implement or to have AI HR. Helpdesk in Bestlink College of the Philippines